Tikrari Method to Improve Memorization Qur’an at MI Al-Huda Sidoarjo - Valensiana Ustoyo; Lailatuz Zuhro; Mufidatus Sholikhah (Institut Agama Islam Tribakti Kediri, 2020)
This research is a classroom action research that aims to improve students' memorization ability in fourth grade A class at MI Al Huda Sidoarjo. The material is